Guide to advanced software testing - Hass, Anne Mette Jonassen (Artech House, 2014)
Taking professionals on a complete tour of this increasingly important, multi-dimensional area, this heavily illustrated book offers a practical understanding of all the most critical software testing topics and their relationships and inter-dependencies. --